Employment concentration, dispersion, and the changing commute in the San Francisco Bay Area - Evelyn Blumenberg; Samuel Speroni (Journal of Transport and Land Use)
In the first decade and a half of the twenty-first century, the San Francisco Bay Area experienced rapid job growth (17% from 2002 to 2015). Employment growth greatly exceeded housing production, resulting in rising housing prices. The mismatch between jobs and housing potentially contributed to an increase in commute distance, as workers relocated to outlying neighborhoods in search of affordable housing. In this paper, the authors analyze changes in commute distance over time, with a focus on the spatial location of employment and, in particular, downtown job growth. They find that commute distance increased slightly between 2002 and 2015 throughout the Bay Area (from 17.2 to 17.8 mi.), with the greatest increase among workers in job centers located in outlying parts of the region (from 19.1 to 20.8 mi.). Increases in census tract jobs was by far the strongest predictor of commute distance increase, though this overall relationship in the region was likely moderated by the increase in employment in downtown San Francisco (44%) where, all else being equal, workers travel shorter distances (14.4 mi. in 2002 and 15.4 mi. in 2015) relative to other workers. This relationship may be due to the demographic composition of San Francisco residents: high-wage, young, single workers who are able to afford high-priced housing close to downtown. A better balance between jobs and housing would allow workers the option of self-selecting into neighborhoods closer to their jobs, underscoring the importance of policies to spur housing production in high-cost metropolitan areas.